Al-Bu’du al-Tajdidi fi ‘ardi Mabahits al-Iman fi Rasail al-Nur - Sujiat Zubaidi Sholeh; Dahniar Maharani (Universitas Darussalam Gontor, 2019)
Keeping faith is a basic need for Muslims in a meaningful manner, so that this activity cannot be separated from the lives of each individual. On the other hand, the development of the era with several shifts in values maked to shift the position of this need. Which requires a renewal in the method of presenting it according to the times. So in this study, the researcher tried to analyze the method of Bediuzzaman Said Nursi with his Rasail Nur in presenting a study of faith that is in accordance with this era as a manifestation of renewal of Islamic thought. This method which is different from the methods initiated by the previous scholars does not only contain theory, but also the applicative guidance of the theory. In theory, Ustadz Nursi explained it with methods: (1) it does not enter into thedebate of the kalam cleric (2) calls on reason and heart (3) concludes with modern natural science (4) focuses on contemporary issues (5) repetition and analogy (6) call to action. And applicatively, he mobilized to: (1) focus on devotion to the Qur’an and faith (2) maintain real sincerity in everyday life (3) maintain ukhuwah Islamiyah and strengthen jama’ah.